2019
DOI: 10.1891/1078-4535.25.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Slogans: Understanding the Ecological Consciousness of Nurses to Advance Ecological Knowledge and Practice

Abstract: Despite unprecedented global environmental changes with widespread health effects, and rapid advances in nursing knowledge and education, the concept of environment within the discipline remains restricted. Environmental health continues to be marginalized in nursing education and practice, with nurses struggling to get beyond the slogans to arrive at practical applications. Framed by ecohealth and radical ecopsychology theory (concerned with nature connection, individual wellness, and social/earth justice), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The lack of Canadian based research on nursing activism for environmental health may be related to a lack of environmental health focus in current Canadian nursing practice. Hanley and Jakubec’s (2019) study confirmed the lack of environmental health focus for Canadian nurses, and their study participants stated environmental health concepts should be incorporated into the undergraduate curriculum to address the knowledge-practice gap.…”
Section: Nurses Role In Environmental Healthmentioning
confidence: 53%
“…The lack of Canadian based research on nursing activism for environmental health may be related to a lack of environmental health focus in current Canadian nursing practice. Hanley and Jakubec’s (2019) study confirmed the lack of environmental health focus for Canadian nurses, and their study participants stated environmental health concepts should be incorporated into the undergraduate curriculum to address the knowledge-practice gap.…”
Section: Nurses Role In Environmental Healthmentioning
confidence: 53%
“…The positive attitudes seen in these quantitative studies were reflected in qualitative research, wherein students suggested that nurses' work can contribute to a sustainable healthcare system through research, leadership and education (Anåker et al., 2021; Ergin et al., 2021). Congruently, Hanley and Jakubec (2019) found that Canadian students and educators advocated for planetary health promotion. Conversely, some studies found that students felt that sustainability and climate change were not a nurse's responsibility (Felicilda‐Reynaldo et al., 2018; Nigatu et al., 2014; Ryan et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Students and educators expressed a need for more frequent and in‐depth sustainability education, embedded throughout the nursing curriculum so that the relevance to nursing would be explicit (Anåker et al., 2021; Chen & Price, 2020; Hanley & Jakubec, 2019). Peres et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community health nursing and nursing education and practice overall in Canada have largely neglected the environmental (or ecological) context of health and its equity dimensions. While there are notable exceptions (e.g., Morin et al, 2022), environmental health and equity remain at the margins (Hanley & Jakubec, 2019). Yet, the health inequities CHNs are called on to help ameliorate are inextricably linked to geography, space, place, and land (Waldron, 2018).…”
Section: Introductionmentioning
confidence: 99%